Hydrodynamic study of drying on Qisthi Hindi using a Fluidized Bed Dryer - Nanang Ruhyat; Haris Ilman Fiqih; Jessi Ray Mardhatilla; Firman Maulana; Fajar Anggara; Dewi Murniati (Journal of Integrated and Advanced Engineering (JIAE), 2022)
A Fluidized Bed Dryer (FBD) is one of the most efficient and prominent moisture-reducing dryers in the food, chemical, and pharmaceutical industries. This work investigates changes in moisture content and drying rate in the FBD with a dense bed as a perforated plate and uses an indirect heating medium. Here the air flows by the blower and acts as a dryer after passing through the heater to reduce the moisture content contained in the material. Qisthi Hindi can be used as herbal medicine for several diseases such as asthma, cough, diabetes, and liver and stomach problems. It can even be consumed during the COVID-19 pandemic. The Qisthi Hindi root has a fairly high calcium and protein content, so drying must be carried out at moderate temperatures because it is a heat-sensitive material. Drying using FBD is carried out at temperatures ranging from 50-100 °C. On air drying at 50 °C, the protein content increased by 3.13%, calcium content increased by 29% from the levels before drying, and water content decreased by 5.3%. At the drying air temperature of 100 °C, the protein content decreased to 3.87%, and the calcium content decreased by 15% from drying at 50 °C. FBD reduced the moisture content significantly in Qisthi Hindi, which is heat sensitive.